2017
DOI: 10.1093/ecco-jcc/jjx096
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor-2 Ameliorates Inflammation in Murine Model of Crohn’s Disease

Abstract: In summary, the endocannabinoid system is induced in murine ileitis but is downregulated in chronic murine and human intestinal inflammation, and CB2R activation attenuates murine ileitis, establishing an anti-inflammatory role of the endocannabinoid system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 53 publications
2
29
1
1
Order By: Relevance
“…Cannabinoid receptors include cannabinoid 1 receptor (CB1R) and cannabinoid 2 receptor (CB2R) [ 4 ]. CB2R belongs to the G-protein–coupled receptor family, and is induced by active inflammation in both humans and mice [ 5 ]. It is mainly expressed in cells associated with innate immunity, such as microglia, astrocytes, neutrophils, macrophages, and myofibroblasts [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoid receptors include cannabinoid 1 receptor (CB1R) and cannabinoid 2 receptor (CB2R) [ 4 ]. CB2R belongs to the G-protein–coupled receptor family, and is induced by active inflammation in both humans and mice [ 5 ]. It is mainly expressed in cells associated with innate immunity, such as microglia, astrocytes, neutrophils, macrophages, and myofibroblasts [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly expressed in cells associated with innate immunity, such as microglia, astrocytes, neutrophils, macrophages, and myofibroblasts [ 6 8 ]. Studies in recent years have demonstrated that CB2R plays a key anti-inflammatory role in many inflammatory diseases and autoimmune diseases, such as inflammatory bowel disease [ 5 ], inflammatory kidney disease [ 9 ], periodontitis [ 10 ] and neuroinflammation [ 6 , 11 ]. Our previous findings suggested that CB2R exhibited specific temporal changes in neutrophils, macrophages and myofibroblasts in a mouse model of an incised skin wound [ 7 ], and ameliorated wound healing by attenuating inflammation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, to the best of our knowledge, no one has considered the neurogenic capacity of AEA and 2‐AG in the adult ENS, several studies have examined more broadly the impact of these molecules in murine colitis. It appears that CB1 and CB2 receptor knockout mice are more susceptible to TNBS colitis, but other work has contradicted the conclusion that the CB2 receptor is protective in the TNF ΔARE/+ model of Crohn's disease .…”
Section: Potential Neurogenic Pathwaysmentioning
confidence: 99%
“…Despite intensive research in recent years, the exact pathogenesis of IBD remains elusive. Our current understanding of the molecular mechanisms involved in IBD has come from chemically, transgenic, and knockout‐induced mouse models . Although mouse models of IBD do not fully recapitulate the human disease, interleukin‐10 knockout (IL‐10 −/− ) mice display similar characteristics to those of human CD .…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of the molecular mechanisms involved in IBD has come from chemically, transgenic, and knockout-induced mouse models. [3][4][5] Although mouse models of IBD do not fully recapitulate the human disease, interleukin-10 knockout (IL-10 −/− ) mice display similar characteristics to those of human CD. 6,7 Under specific pathogen-free (SPF) conditions, IL-10 −/− mice spontaneously develop Crohn's-like chronic colitis characterized by massive infiltration of activated lymphocytes and macrophages in the lamina propria (LP) of the colon.…”
Section: Introductionmentioning
confidence: 99%